2017
DOI: 10.4312/dp.44.1
|View full text |Cite
|
Sign up to set email alerts
|

Niche Construction and Theory of Agricultural Origins. Case studies in punctuated equilibrium

Abstract: IntroductionA central challenge to the theory of agricultural origins (TAO) concerns the integration and joint interpretation of the increasingly large amounts of numeric empirical data made available by participating scientific disciplines, for example, cultural studies, archaeobotany, archaeozoology, plant and animal genetics, radiometric dating, palaeogeography, palaeoclimatology, and others. In a recently published study, Kristen Gremillion et al. (2014) have argued that it may be possible to unify the sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Some interpret this as a slow and gradual process based on cultural (millennial) timescales (e.g., Fuller et al, 2012;Asouti and Fuller, 2013), and others see it as a rapid process over much shorter biological (decadal) timescales (e.g., Hillman and Davies, 1990;Honne and Heun, 2009;Heun et al, 2012). A recent reanalysis (Weninger, 2017) of published archaeobotanical and archaeozoological data indicates that the wild-domesticate transition (WDT) occurred (1) abruptly at around 10.2±0.2 ka BP, (2) simultaneously (within given error limits) for plants and animals, and (3) synchronously with the abrupt onset of moist conditions in the Near East (Schmiedl et al, 2010;Sharifi et al 2015). It appears that, in terms of understanding the introduction of farming and stock-breeding, past research placed too much emphasis on the Younger Dryas (YD), given that the YD ended as much as 1500 years before the WDT.…”
Section: Archaeological Importancementioning
confidence: 99%
“…Some interpret this as a slow and gradual process based on cultural (millennial) timescales (e.g., Fuller et al, 2012;Asouti and Fuller, 2013), and others see it as a rapid process over much shorter biological (decadal) timescales (e.g., Hillman and Davies, 1990;Honne and Heun, 2009;Heun et al, 2012). A recent reanalysis (Weninger, 2017) of published archaeobotanical and archaeozoological data indicates that the wild-domesticate transition (WDT) occurred (1) abruptly at around 10.2±0.2 ka BP, (2) simultaneously (within given error limits) for plants and animals, and (3) synchronously with the abrupt onset of moist conditions in the Near East (Schmiedl et al, 2010;Sharifi et al 2015). It appears that, in terms of understanding the introduction of farming and stock-breeding, past research placed too much emphasis on the Younger Dryas (YD), given that the YD ended as much as 1500 years before the WDT.…”
Section: Archaeological Importancementioning
confidence: 99%
“…After the end of the YD, the potential impact of a series of rapid climate change (RCC) events through the Holocene caused by massive meltwater pulses into the North Atlantic (Mayewski et al, 2004) also needs to be considered. While a putative 10.2 ka RCC event appears to have adversely impacted human communities in the Western Fertile Crescent region of Jordan, Israel and western Syria (Weninger et al, 2009;Borrell et al, 2015;Weninger, 2017), our evidence from the Eastern Fertile Crescent is insufficient to address this issue. While we need to exercise extreme caution in attributing causality and the shortage of secure and refined dates is a major problem (Flohr et al, 2016), we note that the 9.2 ka RCC event coincides in broad chronological terms with a significant interruption in and relocation of human settlements across the Zagros Mountains.…”
Section: Human-environment Interactions At the Dawn Of Settlements In...mentioning
confidence: 76%
“…Both positions are supposedly supported by 14C-radiometric data, but which is of generally low quality. A recent chronological re-analysis [78] of the archeological, archeobotanical and archeozoological data confirmed that the wild-domestic-transition (WDT) was indeed initially slow (millennial scale), but terminated at 10.2 ± 0.2 ka calBP with an abrupt switch to herding and agriculture. Interestingly, the WDT is itself synchronous with an abrupt climatic switch to higher precipitation, as documented in marine and terrestrial climate records in the Mediterranean and adjacent regions (e.g., Levant, Iran).…”
Section: Modeling Human Existence Potential (Hep) and Dispersal By Komentioning
confidence: 92%